Dampak Event MotoGP terhadap Penyewaan Transportasi dan Penjualan Paket Tour pada PT Lombok Trans - Henderi Yadi Dorak; Darmaesti Darmaesti; Sugiman Sugiman (Jurnal Perhotelan dan Pariwisata, 2026)
International tourism events play an important role in stimulating regional tourism development and supporting the local tourism industry. One of the most significant international events held in Indonesia is the MotoGP Mandalika event in Lombok, West Nusa Tenggara. The event attracts a large number of domestic and international tourists, creating opportunities for tourism businesses such as transportation services and tour packages. This study aims to analyze the impact of the MotoGP event on transportation rentals and tour package sales at PT Lombok Trans. The research employed a descriptive qualitative approach with data collection methods including observation, interviews, documentation, and literature review. The results show that the MotoGP Mandalika event significantly increased tourist arrivals, which directly influenced the demand for transportation rentals and tour packages offered by PT Lombok Trans. Data from the company indicates that during the MotoGP event period in 2024, transportation rentals and tour package sales experienced a significant increase compared to regular tourism periods. The findings also reveal that international events such as MotoGP create multiplier effects on tourism businesses by increasing tourist mobility, economic activity, and service demand. Therefore, tourism stakeholders need to develop strategic planning and service readiness to maximize opportunities from international events in the future.